Rosiglitazone Attenuated Endothelin-1-Induced Vasoconstriction of Pulmonary Arteries in the Rat Model of Pulmonary Arterial Hypertension via Differential Regulation of ET-1 Receptors - Yahan Liu; Xiao Yu Tian; Yu Huang; Nanping Wang (PPAR Research)
Pulmonary arterial hypertension (PAH) is a fatal disease characterized by a progressive increase in pulmonary arterial pressure leading to right ventricular failure and death. Activation of the endothelin (ET)-1 system has been demonstrated in plasma and lung tissue of PAH patients as well as in animal models of PAH. Recently, peroxisome proliferator-activated receptor γ (PPARγ) agonists have been shown to ameliorate PAH. The present study aimed to investigate the mechanism for the antivasoconstrictive effects of rosiglitazone in response to ET-1 in PAH. Sprague-Dawley rats were exposed to chronic hypoxia (10% oxygen) for 3 weeks. Pulmonary arteries from PAH rats showed an enhanced vasoconstriction in response to ET-1. Treatment with PPARγ agonist rosiglitazone (20 mg/kg per day) with oral gavage for 3 days attenuated the vasocontractive effect of ET-1. The effect of rosiglitazone was lost in the presence of L-NAME, indicating a nitric oxide-dependent mechanism. Western blotting revealed that rosiglitazone increased ETBR but decreased ETAR level in pulmonary arteries from PAH rats. ETBR antagonist A192621 diminished the effect of rosiglitazone on ET-1-induced contraction. These results demonstrated that rosiglitazone attenuated ET-1-induced pulmonary vasoconstriction in PAH through differential regulation of the subtypes of ET-1 receptors and, thus, provided a new mechanism for the therapeutic use of PPARγ agonists in PAH.